UPAYA PENINGKATAN KEMAMPUAN GURU DALAM PENGGUNAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DI TK AISYIYAH KOTA DUMAI - Wernely Wernely (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This school action research aims to improve the ability of teachers in the use of Information and CommunicationTechnology (ICT) in the learning process. This research was conducted in 4 stages, namely planning, execution,observation and reflection, and carried out in at least two cycles. In this first cycle, one workshop meeting isheld. this first cycle researchers directly observed the improvement of teacher competence in using ICT as ateaching medium. The result of this observation in cycle I, the score reaches the score 27. The acquisition scoreshave exceeded the expectant score of 25, but still far meet the maximum score of 36. But even so theimplementation of ICT workshops in improving teacher competence in the use of ICT as a medium teaching incycle I goes well enough. Results from the observation in cycle II showed an increase, as evidenced from theachievement of the observation result score is 35. The score is higher than expectation score of 25. It proves thatthe implementation of ICT workshop in improving teacher competence in terms of the use of ICT as a medium ofteaching on this cycle II has been running as expectations.